Scientific determinism and the quest for a complete unified theory of biology - Jacob J (2nd International Congress of plant physiology on sustainable plant productivity under changing environment 8-12 January, 2003, New Delhi)
The famous uncertainty principle of Werner Heisenberg which suggests that the greater the precision of the estimation of the mass of a particle, the lesser the accuracy (i.e. the more the uncertaintyO of estimation of its velocity and vice-versa put an end to scientific determinism in physics. The closest biological equivalent of Heisenbergs uncertainty principle is the existence of biological/genetic diversity, which is as fundamental and inescapable a characteristic of the biological world as the uncertainty principle of the physical world. This paper demonstrates examples of how biological diversity brings with it an element of uncertainty and conflicting priorities compromise the performance of plants. A plant variety with high water use efficiency and favourable stable isotopic signatures in its dry matter or a transgenic plant with additional copies of antioxidant genes might tolerate stress better, but biomass may be highly compromised.
Keywords: Scientific determinism